Does Swallow Droppings and NPK Fertilizer Have a Good Impact on Onion Growth And Results on Peat? - Adam Bramantara Putra; Erik Cahyono (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Shallots are one of the horticultural commodities that are very often used to be a flavoring for dishes. Tanah peat as a medium for growing shallots has many obstacles including low nutrient availability, low pH, organic matter that has not been decomposed so that the nutrient content especially macro nutrient such as low N, P and K. Usaha to fix it is to give swallow manure and NPK compound fertilizer. The purpose ofthis research is toobtain the interaction of doses of swallow manure and NPK fertilizer for the best growth and yield of shallots on peatlands. This research was carried out on March 7, 2020 to May 9 2020 at Jalan Reformasi, Southeast Pontianak District, Kota Pontianak, West Kalimantan. The design used in this study is a Randomized Designof Factorial Group (RAKF) which consists of 2 factors , namely the first factor is the application of swallow feces consisting of 3 levels , and the second facto isthe application of NPK fertilizer, whose plotconsists of 3 levels with a total of 9 treatments including 20 tons / hectare of swallow manure and 400 kg / hectare of NPK fertilizer, 20 tons of swallow manure and 500 kg/hectare of NPK fertilizer, 20 tons/hectare of swallow manure and 600 kg/hectare of NPK fertilizer, 30 tons/hectare of swallowmanur and 400 kg/hectare of NPK fertilizer, 30 tons/hectare of manure swallows and 500 kg/hectare of NPK fertilizer, 30 tons of swallow manure and 600 kg/hectare of NPK fertilizer, 40 tons/hectare of swallow manure and 400 kg/hectare of NPK fertilizer, 40 tons/hectare of swallow manure and 500 kg/hectare NPK fertilizer, 40 tons/hectare of swallow manure and 600 kg/hectare of NPK fertilizer. The treatment was repeated 3 times, and each experimental unit consisted of 15 plant samples. The variables in this study were planting height, number of leaves per clump, number of saplings per clump, root volume, total dry weight per plant, fresh weight of tubers per clump, dry weight wind tubers per clump, yield per plot, The results of theian research showed that the application of 30 tons / hectare of swallow manure and 400 kg / hectare of NPK fertilizer on shallots was the best interaction dose to increase the yield of fresh weight of bulbs and wind dry weight of tubers.